2008
DOI: 10.1124/jpet.107.136077
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Reactive Oxygen Species and FLICE Inhibitory Protein on Lipofectamine-Induced Apoptosis in Human Lung Epithelial Cells

Abstract: Cationic liposomes such as Lipofectamine (LF) are widely used as nonviral gene delivery vectors; however, their clinical application is limited by their cytotoxicity. These agents have been shown to induce apoptosis as the primary mode of cell death, but their mechanism of action is not well understood. The present study investigated the mechanism of LF-induced apoptosis and examined the role of reactive oxygen species (ROS) in this process. We found that LF induced apoptosis of human epithelial H460 cells thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Some in vitro studies have reported on the cytotoxicity of cationic liposomes (104,105). Additionally, a recent report provides evidence that Lipofectamine induces rapid generation of reactive oxygen species that is required for cFLIP down-regulation and subsequent activation of apoptosis in human lung epithelial cells (106). However, our survival studies showed a marginal influence of Lipofectamine alone on mortality in mice after CLP (52).…”
Section: Potential Anti-apoptotic Therapy In Sepsiscontrasting
confidence: 54%
“…Some in vitro studies have reported on the cytotoxicity of cationic liposomes (104,105). Additionally, a recent report provides evidence that Lipofectamine induces rapid generation of reactive oxygen species that is required for cFLIP down-regulation and subsequent activation of apoptosis in human lung epithelial cells (106). However, our survival studies showed a marginal influence of Lipofectamine alone on mortality in mice after CLP (52).…”
Section: Potential Anti-apoptotic Therapy In Sepsiscontrasting
confidence: 54%
“…19 This might be due to the interaction of cells with fibrin (possibly through integrin a v b 3 ), which may suppress caspase activation and reactive oxygen species generation. 18 Fibrin, a major protein component of blood clots, is able to form a gel at physiological temperatures. It has been used extensively in biomedical engineering applications ranging from cardiovascular tissue engineering 19,20 to wound-healing experiments (due to its biocompatibility and its ability to biodegrade in vivo).…”
mentioning
confidence: 99%
“…Remarkably cells exposed to Lipofectamine showed reduced adherences which led to spherical morphology and may result in early apoptosis. A recent study has reported similar changes in morphology and consequent apoptosis of cultured human lung epithelial cells which were treated with Lipofectamine for 6 h (Kongkaneramit et al 2008). The dependency of the production of reactive oxygen species on Lipofectamine-induced apoptosis has also been described in the mentioned paper.…”
Section: Discussionmentioning
confidence: 53%